TECHNICAL TERMS IN TRANSLATION - Axunbabaeva Nargiza Xamidjanovna (Research Focus International Scientific Journal, 2023)
Technical translation involves specific documents usually produced by professionals with a high level of expertise in their fields. Translators who work in this niche handle texts about the practical application of technological information or scientific research. It’s a challenging job that calls for an in-depth understanding of technical documents, their nature and specific requirements. Technical translation is necessary for multiple fields, from engineering to construction and healthcare. Any errors in the translated texts or missing information can easily lead to costly lawsuits or the need to retranslate your company documentation. Technical documentation is necessary when looking to be compliant with local and international standards. From patents and user manuals to health and safety instructions, these documents are proof of accuracy for every operation and business process.